Oral hairy leukoplakia in a child using a corticosteroid nasal spray - Costa, Fernanda Herrera [UNESP]; Costa, Victor [UNESP]; León, Jorge Esquiche [UNESP]; Anbinder, Ana Lia; Ribeiro-Silva, Alfredo; Kaminagakura, Estela [UNESP] (Wiley, 2020)
We report a case of atypical oral hairy leukoplakia (OHL) in a 9-year-old immunocompetent girl treated with fluticasone propionate nasal spray for allergic rhinitis. The OHL in childhood is uncommon and should be included in a differential diagnosis of white lesions in the oral mucosa.
Keywords: Epstein-Barr virus; in situ hybridization; oral hairy leukoplakia